IMPLEMENTASI PROGRAM BANTUAN PANGAN NON TUNAI (BPNT) DI KECAMATAN CIKIJING KABUPATEN MAJALENGKA - diding bajuri; deni herdiana; suci hotimah (Jurnal Ilmu Administrasi CENDEKIA, 2023)
ABSTRACTThe research method used in this study is a qualitative research method, through informants that the author has determined with the analytical tools used from Meter and Horn in Nugroho, 2009, namely: (1) Interorganizational Communication, (2) Executor Characteristics, (3) Economic Conditions , Social and Political, (4) Executor's Disposition or Attitude.Through the informants that the author has determined regarding the implementation of the BPNT Program in Cikijing District, Majalengka Regency, in general it is running according to the goals and targets set, obstacles in implementing BPNT can be overcome by paying attention to the General Guidelines (Pedum) that have been prepared. Keywords : Implementation, Bantuan Pangan Non Tunai, Non-Cash Food Assistance Program (BPNT)